2012
DOI: 10.1111/j.1742-1241.2012.02906.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptom-based diagnosis of urinary tract infection in women: are we over-prescribing antibiotics?

Abstract: Symptoms alone have low accuracy when assessed against the reference standard for diagnosing UTI. Empiric treatment of UTI based on symptoms may expose large number of patients to unnecessary antibiotics. Wet mount microscopy for presence of pyuria as a 'near patient test' before starting antibiotics seems a rational approach for management of UTI in symptomatic women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…The combination of urgency, burning during micturition, and pyuria was found to be the best predictor of UTI with AUC of 78.48% and +LR 2.97. Pyuria in urinalysis and frequency of sexual intercourse more than 5 times per month in history were found to be significantly associated with positive urine culture [35]. The absence of pyuria was the best predictor for ruling out lower UTI even in symptomatic women (AUC 77.07%, -LR 0.1).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The combination of urgency, burning during micturition, and pyuria was found to be the best predictor of UTI with AUC of 78.48% and +LR 2.97. Pyuria in urinalysis and frequency of sexual intercourse more than 5 times per month in history were found to be significantly associated with positive urine culture [35]. The absence of pyuria was the best predictor for ruling out lower UTI even in symptomatic women (AUC 77.07%, -LR 0.1).…”
Section: Discussionmentioning
confidence: 76%
“…The diagnostic accuracy of urinary symptoms and their combinations for early diagnosis of lower UTIs was described in by Mishra et al [35]. Using the results of the urine culture (> 10 2 colony-forming units (CFU)/mL) as a reference for diagnosis, they have found that urgency, burning sensation during urination, and dysuria were the best predictor symptoms for lower UTI.…”
Section: Discussionmentioning
confidence: 99%
“…Although rUTI in adult women is the leading cause of visits to the doctor's office in the United States [1], the proper management of this condition is not well established because most doctors treat this condition with broad-spectrum antibiotics to ensure a high rate of sterilisation without identifying the bacterial agent by urine culture [5]. We now acknowledge that some patients who present with typical UTI have in fact sterile urine.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it reveals that symptoms alone have low accuracy when assessed against the reference standard for diagnosing UTI. Empiric treatment of UTI based on symptoms may expose large number of patients to unnecessary antibiotics [7]. A study concluded about antibiotic resistance patterns of outpatient pediatric UTI and has concluded that E. coli remains the most common pediatric uropathogen [8].…”
Section: Discussionmentioning
confidence: 99%